Collaborative Learning for EFL Academic Writing Development in Higher Education: A Systematic Literature Review - Sari, Fitria Wulan; Jamilah; Aditama, Madya Giri; Bahara, Susana R; Daud, Abdulhalim (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Academic writing is a central competency in higher education, yet many students struggle to meet the demands of disciplinary courses, particularly in English as a Foreign Language (EFL) context. Collaborative learning, grounded in social constructivist theory, has emerged as a promising pedagogical approach to enhance writing development by fostering interaction, peer feedback, and shared knowledge construction. This systematic literature review synthesizes empirical studies published between 2020 and 2025 that examine the implementation of collaborative learning in higher education settings. This study aims to determine the implementation of collaborative learning in EFL writing classroom (benefits and challenges) using the Systematic Literature Review (SLR) method. The SLR method is employed to rigorously identify, examine, evaluate, and interpret the body of existing research concerning a specified phenomenon, guided by clearly defined research questions. This approach enables the systemic identification of relevant scholarly works, with each phase conducted in accordance with predetermined, standardized procedures or protocols. The results indicate that collaborative learning in EFL writing instruction in higher education context boosts organization, grammar, vocabulary richness, fluency, and the ability to structure idea effectively. The students feel more motivated, confident, and less anxious, aligning with the socio constructivist view that deeper language development emerges through interaction, meaning negotiation, and collaborative problem solving.